Uji Daya Hambat Virgin Coconut Oil Plus terhadap Pertumbuhan Bakteri Streptococcus mutans - Hassan, Ewithya H.; Zuliari, Kustina; Mintjelungan, Christy N. (Universitas Sam Ratulangi, 2019)
Abstract: Dental caries is caused by a variety of factors, and the most important one is bacteria Streptococcus mutans. This disease could be prevented inter alia by using mouthwash. Albeit, mouthwash contains synthetic chemical ingredients which might be harmful to our health. Virgin coconut oil plus (VCO plus) can be used as a herbal medicine to inhibit the growth of bacteria in the oral cavity. This study was aimed to test whether the VCO plus had an inhibitory effect on the growth of Streptococcus mutans. This was an experimental laboratory study, using pure experimental design (true experimental design) with the post test only control design. We used modified Kirby-Bauer method with filter paper. Pure VCO plus obtained from the laboratory at Faculty of Mathematics and Natural Science University of Sam Ratulangi Manado was tested for its inhibitory effect. Erythromycin was used as the positive control and aquadest as the negative control. The results showed that the mean inhibitory zone of VCO plus to Streptococcus mutans was 10.22 mm which was categorized as moderate according to Davis and Stout. The mean inhibitory zone of VCO plus was less than of erythromycin. Conclusion: Virgin coconut oil plus had moderate inhibitory effect to Streptococcus mutans.Keywords: dental caries, virgin coconut oil plus, Streptococcus mutansÂ Abstrak: Karies gigi disebabkan oleh berbagai faktor, namun yang paling berperan yaitu Streptococcus mutans. Salah satu cara untuk mencegah karies gigi, antara lain menggunakan obat kumur. Namun obat kumur yang digunakan saat ini banyak mengandung bahan sintetis yang berefek kurang baik. Bahan alam yang banyak digunakan untuk menghambat pertumbuhan bakteri yaitu virgin coconut oil plus (VCO plus). Penelitian ini bertujuan untuk menguji daya hambat VCO plus terhadap pertumbuhan Streptococcus mutans. Jenis penelitian ialah eksperimental laboratorium, menggunakan rancangan eksperimental murni (true experimental design) dengan post test only control design. Metode yang digunakan ialah modifikasi Kirby-Bauer menggunakan kertas saring. Bahan uji ialah VCO plus yang diperoleh dari laboratorium F-MIPA Univeristas Sam Ratulangi, dengan kontrol positif eritromisin dan kontrol negatif akuades. Hasil penelitian mendapatkan rerata diameter zona hambat VCO plus terhadap Streptococcus mutans sebesar 10,22 mm yang termasuk kategori sedang berdasarkan penggolongan Davis dan Stout. Diameter zona hambat VCO plus lebih kecil dibandingkan dengan diameter zona hambat dari antibiotik (eritromisin). Simpulan: Virgin coconut oil plus mempunyai daya hambat kategori sedang terhadap pertumbuhan Streptococcus mutans.Kata kunci: karies gigi, virgin coconut oil plus, Streptococcus mutans